"Melhor que o Mel, só o Céu": trauma intergeracional, complexo cultural e resiliência na diáspora africana (um estudo de caso do Quilombo do Mel da Pedreira, em Macapá, AP) - Gomes, Antonio Maspoli de Araújo (2017)
The concept of intergenerational historical trauma is a valid concept to understand the impact of genocide, war, terrorist attacks and/or public calamities over certain populations as it was the case, for example, of descendants of survivors from the concentration camp holocaust and descendants of slaves. The theory of cultural complex enables analyses of the intergenerational historical trauma impact on the production of complexes that develop unconsciously on those populations and undermine their resources. This research was based on a mixed method. The analysis of the cultural production of 42 Quilombolas, (men and women from the Quilombola community of Mel da Pedreira, Macapá, in the state ôf Amapá in northern Brazil) was conducted via qualitative and quantitative methods as a result of participant observation, ethnologic and ethnographic observations, semi-guided interviews, content analyses, Adriano Vaz Serra Self-concept Assessment, Rosenberg Self-esteem Scale, and simple statistical, analyses. From these theories, methods and field observations were confirmed the hypotheses below: I. The trauma intergenerational history resulting from the memories of slavery remains present in the narratives and a cultural production of Afro- brazilians. II. The historic trauma intergeracional generates a cultural complex of inferiority in the population maroon. IV. T here was a low self esteem in the population as quilombola symptom of cultural complex. V. The cultural complex negatively affects the way of life of quilombola communities and contributes to the impoverishment of the population. VI. What defines the life in the quilombo is the concept of resistance/resilience. The hypothesis III. T here was a low self-concept in population as quilombola symptom of cultural complex; it is not confirmed. Finally, using the model adapted by Martha Kent and Mary C. Davis, P9Sitive Factors and Resilience Promoters, the Quilombolas scored very well in Six of eight items evaluated. That shows the capacity of Quilombolas to adapt, resist and endure facing extreme adversity imposed by intergenerational trauma, by the cultural complex that generates poverty and by social exclusion